The Effect of Beans Extract (Phaseolus vulgaris L.) to LDL Cholesterol Level in White Rats Hypercholesterolemia Model - Noni Kartika Sari; Ida Nurwati; Danus Hermawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Low Density Lipoprotein (LDL) cholesterol level related with Coronary Heart Disease (CHD) which is the most common death cause in the world. Beans contains flavonoid, phytosterol, saponin, niasin, vitamin C, and fiber which have hypolipidemic effect. This study aimed to determine the effect of beans extract to the LDL cholesterol level in white rats hypercholesterolemia model. Methods: This study was a laboratory experimental research using the posttest only controlled group design, that have done in Histology Laboratorium of Sebelas Maret University Surakarta. Samples of research were 30 male white rats, Wistar strain. Control Group (KK) was given pellets and aquades for 28 days. Group 1 until 4 (KP1-4) were given duck egg yolk 5 gram/200 gram BW white rat/day and PTU 0,01% for 28 days. On days 15-28, Group 2 (KP2) was given simvastatin 0,72 mg/200 gram BW white rat/day, Group 3 was (KP3) given beans extract 100 mg/200 gram BW white rat/day, and Group 4 (KP4) was given beans extract 150 mg/200 gram BW white rat/day. The datas of LDL cholesterol level were analyzed with One-way ANOVA test and Post Hoc test. Result: Result of this study shows that LDL cholesterol levels of KK = 33.83 14.442 mg/dl, KP1 = 54.00 27.943 mg/dl, KP2 = 18.83 7.672 mg/dl, KP3 = 77.33 20.954 mg/dl and KP4 = 80.17 31.923 mg/dl. The statistical analysis with One- way ANOVA shows a significant difference in LDL cholesterol level among the five groups of treatment with p = 0.000 (p < 0.05). Post Hoc Test shows a significant difference in LDL cholesterol level between KP1 KP2 with p = 0.011 (p < 0.05) and non significant difference in LDL cholesterol level between KK KP1 with p = 0.129, KP1 KP3 with p = 0.081, and KP1 KP4 with p = 0.052 (p > 0.05). Conclusions: The beans extract (Phaseolus vulgaris L.) does not give any effect to decrease of the LDL cholesterol level in white rats (Rattus norvegicus) hypercholesterolemia model. Keywords: Beans extract, LDL, Rattus norvegicus, hypercholesterolemia.